1996
DOI: 10.1159/000259187
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Aminoglycoside Antibiotics to Cytotoxins

Abstract: We have previously postulated an enzymatic transformation of gentamicin (to a metabolite or an ‘activated’ molecule) as part of its ototoxic action. Here we test with eight aminoglycosides whether the proposed mechanism applies to these antibiotics as a group. Drugs were activated by incubation with a subcellular fraction from liver, and cytotoxicity was tested in a bioassay using isolated outer hair cells from guinea pig. None of the aminoglycosides compromised the viability of the cells when assayed directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…If the median number of courses taken by all CF subjects are used as an estimate for x then, from Table 1 While this single exponential estimate has some practical utility, it is probably suboptimal. Experimental work (2,12,15,19,43) strongly suggests that AGs accumulate in cochlear sensory cells. Consequently, a better estimate would be provided by an equation including additional terms that models a cumulative component of risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the median number of courses taken by all CF subjects are used as an estimate for x then, from Table 1 While this single exponential estimate has some practical utility, it is probably suboptimal. Experimental work (2,12,15,19,43) strongly suggests that AGs accumulate in cochlear sensory cells. Consequently, a better estimate would be provided by an equation including additional terms that models a cumulative component of risk.…”
Section: Resultsmentioning
confidence: 99%
“…2 suggest an idiosyncratic response to repeated AG exposure. This absence of a linear relationship is likely to reflect the multifactorial contribution to the onset and progression of AG-induced hearing loss (2,4,12,15,18,19,28,43). This idea is supported by a number of distinct pharmacokinetic and biochemical processes identified from experimentally induced cochleotoxicity outlined below.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sha and Schacht (1999) found that a cytotoxic metabolite produced after initial exposure to AG generates free radicals in a chain reaction. Crann and Schacht (1996) found thatAGs form a secondary toxic compound within the cochlea itself. The combined effects of prolonged AG retention in the cochlea and cochlear conversion of AGs into a toxic metabolite contribute to the delayed component of AG-induced hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some investigators have postulated a metabolic transformation or activation to produce a molecular species derived from the antibiotic which may show greater toxicity than the drug itself, or alternatively these derivatives may act in combination with the antibiotic, producing the ototoxic effect [1]. Studies with kanamycin [2], gentamicin [3,4] and streptomycin (STP) [5] have been performed, but the resulting metabolites have not been identified and characterized.…”
Section: Introductionmentioning
confidence: 99%